Impact of Patient Socioeconomic Disparities on Time to Tympanostomy Tube Placement. (February 2022) - McCoy, Jennifer L.; Dixit, Ronak; Lin, R. Jun; Belsky, Michael A.; Shaffer, Amber D.; Chi, David; Jabbour, Noel
Objectives: Extensive literature exists documenting disparities in access to healthcare for patients with lower socioeconomic status (SES). The objective of this study was to examine access disparities and differences in surgical wait times in children with the most common pediatric otolaryngologic surgery, tympanostomy tubes (TT). Methods: A retrospective cohort study was performed at a tertiary children's hospital. Children ages <18 years who received a first set of tympanostomy tubes during 2015 were studied. Patient demographics and markers of SES including zip code, health insurance type, and appointment no-shows were recorded. Clinical measures included risk factors, symptoms, and age at presentation and first TT. Results: A total of 969 patients were included. Average age at surgery was 2.11 years. Almost 90% were white and 67.5% had private insurance. Patients with public insurance, ≥1 no-show appointment, and who lived in zip codes with the median income below the United States median had a longer period from otologic consult and preoperative clinic to TT, but no differences were seen in race. Those with public insurance had their surgery at an older age than those with private insurance ( P < .001) and were more likely to have chronic otitis media with effusion as their indication for surgery (OR: 1.8, 95% CI: 1.2-2.5, P = .003). Conclusions: Lower SES is associated with chronic otitis media with effusion and a longer wait time from otologic consult and preoperative clinic to TT placement. By being transparent in socioeconomic disparities, we can begin to expose systemic problems and move forward with interventions. Level of Evidence: 4